(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fauziah I, Asmara W, Wahyuni AETH, Widayanti R. 2021. Short Communication: PCR detection of Avibacterium paragallinarum from layers with infectious coryza symptoms in poultry farms of Sleman District, Indonesia. Biodiversitas 22: 4890-4894. Infectious coryza (IC), caused by Avibacterium paragallinarum, is a contagious and infectious respiratory tract disease that affects the commercial poultry industry. Molecular techniques, such as species-specific PCR, HPG-2 PCR are mostly used for the detection of A. paragallinarum. The current research was carried out to isolate A. paragallinarum from the layers of infectious coryza signs in Sleman District, special region of Yogyakarta, followed by PCR confirmation of the identified bacteria. Nine field isolates were observed and determined based on their colony and cell morphology. All isolates were characterized biochemically and confirmed with species-specific HPG-2 PCR for A. paragallinarum. Out of 9 isolates, 6 (66.7%) isolates were biochemically identified as A. paragallinarum and confirmed by HPG-2 PCR.